Changement climatique et atrophie des masses glaciaires : quelles mutations pour les paysages islandais ? - Marie Chenet; Erwan Roussel (EchoGéo)
The Global Warming which occurs since the end of the Little Ice Age in Iceland leads to the retreat of the glacier fronts. This retreat has induced new dynamics in the glacier foreland, especially related to glacial meltwater and post-glacial release. Lichenometrics measures on moraines ridges and paleosandurs provide us the opportunity to reconstruct the evolution of the proglacial areas of the Morsárjökull and the Skaftafellsjökull (South-east Iceland) since the end of the Little Ice Age. Important processes of rockslides and rockfalls occur on slopes, whereas proglacial rivers undergo phenomena of incision and abandon of minor channels.